Dietary patterns, nutrients, and risk of expiratory airflow limitation in children and adolescents. - Bao, Yijing; Chang, Qing; Zhang, Han; Ding, Huiyuan; Gao, Jing; Zhang, Chuyang; Chi, Baofeng; Xia, Yang; Zhao, Yuhong; Zhang, Hehua (European Journal of Nutrition, 2025)
Background: Increasing global pediatric respiratory diseases require understanding modifiable factors affecting lung function. We explored the association between dietary patterns, nutrients and the risk of expiratory airflow limitation (EAL) in children and adolescents. Methods: Dietary intake was collected using a validated food frequency questionnaire (FFQ) with 110 food items. Factor analysis was employed to determine dietary patterns. Pulmonary function was measured using a medical-grade pulmonary function analyzer. EAL was defined as the ratio of Forced Expiratory Volume in one second to Forced Vital Capacity (FEV1/FVC) < 0.8. Results: A total of 611 EAL cases occurred in 3,204 participants, with a prevalence of 19.07%. Four primary dietary patterns were identified (animal, healthy, sweet, and plant foods), which explained 44% of the variance in food consumption. The plant foods pattern (fourth quartile vs. first quartile intake) was associated with a reduced risk of EAL (Odds Ratio [OR] = 0.71, 95% Confidence Interval [CI]: 0.53, 0.94; Pfor trend < 0.02). Higher fruit consumption (high vs. low) in plant foods pattern was associated with lower EAL risk (OR = 0.79, 95% CI: 0.62, 0.99, Pfor trend = 0.04). Every standard deviation increase in foods (Chinese sauerkraut, pickled foods) and nutrients (total dietary fiber, soluble dietary fiber, and pyridoxine) in plant foods was all positively associated with FEV1 /FVC (all P < 0.05). Conclusions: Long-term intake of plant foods pattern enriched with dietary fiber and pyridoxine is promising for lung function protection in children and adolescents.